(untitled) (INGE@UAN - TENDENCIAS EN LA INGENIERÍA, 2014)
This paper shows the results of DVB-RCS2 standard evaluation for inbound satellite links between 2 Mbps and 10 Mbps in Peru, using Ka Band High Throughput Satellite. We perform predictive calculation for rain attenuation rates by mathematical models of recommendations P.618, P.838, P.837 from ITU, these results are used as input data for development of link budgets, in which the modulation schemes and existing coding from DVB-RCS2 standard are evaluated. The research aims to anticipate operating levels in a satellite return link in Ka band with rain conditions, considering the need for deployment of broadband services on the Peruvian territory, in complement with terrestrial technologies.